NanoART synthesis, characterization, uptake, release and toxicology for human monocyte—macrophage drug delivery - Nowacek, Ari S (2009)
BACKGROUND: Factors limiting the efficacy of conventional antiretroviral therapy for HIV-1 infection include treatment adherence, pharmacokinetics and penetration into viral sanctuaries. These affect the rate of viral mutation and drug resistance. In attempts to bypass such limitations, nanoparticles containing ritonavir, indinavir and efavirenz (described as nanoART) were manufactured to assess macrophage-based drug delivery. METHODS: NanoART were made by high-pressure homogenization of crystalline drug with various surfactants. Size, charge and shape of the nanoparticles were assessed. Monocyte-derived macrophage nanoART uptake, drug release, migration and cytotoxicity were determined. Drug levels were measured by reverse-phase high-performance liquid chromatography. RESULTS: Efficient monocyte-derived macrophage cytoplasmic vesicle uptake in less than 30 min based on size, charge and coating was observed. Antiretroviral drugs were released over 14 days and showed dose-dependent reduction in progeny virion production and HIV-1 p24 antigen. Cytotoxicities resulting from nanoART carriage were limited. CONCLUSION: These results support the continued development of macrophage-mediated nanoART carriage for HIV-1 disease.